Polymorphisms in ACE and ACTN3 genes and blood pressure response to acute exercise in elite male athletes from Serbia - Durmic, T. S.; Zdravkovic, M. D.; Djelic, M. N.; Gavrilovic, T. D.; Djordjevic Saranovic, S. A.; Plavsic, J. D.; Mirkovic, S. V.; Batinic, D. V.; Antic, M. N.; Mihailovic, Z. R.; Atanasijevic, N. G.; Mileusnic, M. J.; et al. (The Tohoku Journal of Experimental Medicine, 2018)
Physiological adaptations to various types of prolonged and intensive physical activity, as seen in elite athletes from different sports, include changes in blood pressure (BP) response to acute exercise. Also, functional polymorphisms of the angiotensin I converting enzyme (ACE) and alfa-actinin-3 (ACTN3) genes are shown to be associated with BP parameters changes, both in athletes and sedentary population. In this study, an Alu insertion (I)/deletion (D) polymorphism in ACE gene, as well as nonsense mutation in the gene encoding ACTN3 have been scored in 107 elite Serbian athletes classified according to their sporting discipline to power/sprint (short distance runners/swimmers), endurance (rowers, footballers, middle-distance swimmers) or mixed sports (water polo, handball, volleyball players). Presence of nonfunctional allele in ACTN3 is associated with significantly increased maximal systolic BP (SBPmax, p = 0.04). Athletes with Alu insertion in ACE had significantly (p = 0.006) larger decline of systolic BP after 3 minutes of recovery (SBPR3), calculated as the percentage of maximal SBP response during exercise stress testing. Concomitant presence of non-functional variant in ACTN3 gene decreased this beneficiary effect of ACE mutation on SBPR3. Long term enrollment in power/sprint sports significantly increased resting diastolic BP (DBPrest: 74 mmHg) and SBPmax (197 mmHg) and improved SBPR3 (74.8%) compared to enrolment in endurance (72 mmHg; 178 mmHg; 81.1%) and mixed sports (69 mmHg; 185 mmHg; 80.0%). Lack of the effect of genotype by sport interaction on BP parameters suggests that the long-term effects of different disciplines on BP are not mediated by these two genes.